ANALISISIS PERSEPSI STRES KERJA TENAGA KESEHATAN DI MASA PANDEMI COVID-19 DI RUMAH SAKIT â€œXâ€ DI SUMATERA SELATAN TAHUN 2021 - Santi Rosalina; Heriziana Heriziana (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
The COVID-19 pandemic has had a profound effect on all aspects of society, including mental health and physical health. WHO and public health authorities around the world are acting to control the COVID-19 outbreak. However, this time of crisis creates stress throughout the population. Fear and anxiety about this new disease, plus other factors can influence job stress (WHO, 2021). "The high risk of suffering from burnout syndrome due to exposure to unusually severe stress in health facilities during this pandemic can have long-term effects on the quality of medical services because these health workers can feel depressed, extreme fatigue and even feel less competent in carrying out their duties, and this is certainly have an unfavorable impact on our efforts to combat COVID-19," (FKUI, 2020). This research is about the perception of work stress of health workers at Hospital 'X' in South Sumatra. The purpose of this study was to analyze the perception of work stress for Health Workers at Hospital 'X' in South Sumatra during the Covid-19 pandemic. The type of research used is correlation research. The results of the study show that the company's regulation (X1) has a significance value of 0.743 > 0.05 which means that the company's regulation (X1) has no effect on symptoms of stress (Y) Anxiety (X2) has a significance value of 0.461 > 0.05 which means that Worries (X2) do not affect the symptoms of stress (Y) Workload (X3) a significance value of 0.007 <0.05, it means that there is an effect of workload (X3) on symptoms of stress. Workload and working conditions affect the symptoms of stress in health workers because excessive workload causes pressure and can cause stress. Keywords : Work Stress, Health Workers, Covid-19 Pandemic